A review on eminent application and performance of nano based silica and silica fume in the cement concrete. (March 2023) - Vijayan, Dhanasingh Sivalinga; Devarajan, Parthiban; Sivasuriyan, Arvindan
Highlights: Pozzolanic activity of nano-silica is exceptionally high. The filling effect of nano-silica has a significant impact on the process of pore structure refining. Utilizing Silica fume improves corrosive strength, sulphate resistance, and abrasion resistance. Silica fume reduces concrete's permeability and improves its durability. Nano-silica can improve concrete's mechanical and durability properties and its boosts concrete compressive strength. Abstract: In last few years, the revolution of nanotechnology has escalated great in varied science streams. In the, study of effective utilization of Nano particles in construction industry has become a conspicuous one. While implementing the sustainability in construction, the adoption of nanotechnology has done a greater impact and there is still need more to explore. The Nano particles are usually possess incredible physical and chemical properties that enable it to use as a better constructionmaterials which help to enhance the properties like strength, durability and rheology of concrete and it also helps to counteract the environmental pollution. Additionally, the cement based materials which is prepared along with Nanomaterial helps to assess and examine the resistance towards deterioration in concrete and the extent of rebar corrosion. This paper reviews the literature on the nanotechnology application particularly in the construction industry. At first, the preliminary details of nanotechnology have been discussed and then, it exclusively focuses the effective nanoparticles like Silica fume and Nano silica which are proved as a ready thing to improve the property of concrete.